Procedural Deviations in Small-Scale Land Acquisition as Unlawful Acts in Corruption Offences - Syawal Abdulajid; Anshar Anshar; Ainurrafiqa Pelupessy (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
Small-scale land acquisition constitutes a legal mechanism designed to ensure flexibility and efficiency in the implementation of development projects serving the public interest. The procedural simplification inherent in this regime is intended to respond to urgent development needs that directly affect local communities. In practice, however, such simplification is frequently misconstrued as the elimination of normative legal requirements, thereby creating opportunities for procedural deviations that may result in state financial losses. This condition raises complex legal issues when administrative irregularities shift into the domain of corruption offences. This article examines how procedural deviations in small-scale land acquisition may be legally constructed as unlawful acts within the framework of corruption crimes. The research adopts a normative legal method, employing statutory and case approaches, grounded in findings from the analysis of small-scale land acquisition practices in public-interest development projects. The analysis focuses on the normative limits of procedural simplification, the concept of unlawfulness in both formal and material senses, and the construction of criminal liability based on mens rea and abuse of authority. The findings demonstrate that procedural deviations in small-scale land acquisition cannot automatically be classified as criminal acts. Nevertheless, where such deviations violate fundamental land acquisition norms, are accompanied by an abuse of authority, and result in state financial losses, they may fulfil the elements of unlawfulness in corruption offences, particularly as regulated under Articles 2 and 3 of the Indonesian Anti-Corruption Law. This article underscores the necessity of positioning criminal law as ultimum remedium to prevent the criminalisation of public policy, while simultaneously reinforcing its preventive function in safeguarding the integrity and accountability of the land acquisition system for public development.